The Experience of Sleep Problems and Their Treatment in Young People at Ultra-High Risk of Psychosis: A Thematic Analysis - Waite, Felicity; Bradley, Jonathan; Chadwick, Eleanor; Reeve, Sarah; Bird, Jessica C.; Freeman, Daniel (Frontiers in Psychiatry, 2018)
We view sleep disruption as a contributory causal factor in the development of psychotic experiences. Clinical trials indicate that psychological interventions targeting insomnia result in improvements in both sleep and psychotic experiences. The aim of this study was to gain the perspective of young people at ultra-high risk of psychosis on their sleep problems and associated psychological treatment. Interviews were conducted with 11 patients, aged 15-22 years, at ultra-high risk of psychosis who had received a psychological sleep intervention. Responses were analysed using thematic analysis. Disrupted sleep timing and a lack of routine were the characteristic hallmarks of participants’ sleep problems. Sleep disturbance, psychological wellbeing, and functioning had a reciprocal relationship. There were negative expectations prior to therapy, however meaningful improvements occurred in sleep, mood, and functioning. The active implementation of therapy techniques was highlighted as important. These findings indicate that the treatment of sleep problems is highly valued and has a meaningful impact on wellbeing in young people at ultra-high risk of psychosis.